Multiband supercontinuum generation in an air-core revolver fibre. (July 2017) - Yatsenko, Yu.P.; Pleteneva, E.N.; Okhrimchuk, A.G.; Gladyshev, A.V.; Kosolapov, A.F.; Kolyadin, A.N.; Bufetov, I.A.
Abstract: Multiband supercontinuum generation in an air-core revolver fibre having a large number of transmission bands in a wide spectral range has been studied experimentally and theoretically for the first time. The fibre fabricated by us possesses unique dispersion and guidance characteristics for radiation transfer from one band to another despite the high losses at the band boundaries. In our experiments, launching 205-fs laser pulses of 110 μJ energy at 1028 nm into the fibre we have obtained a supercontinuum spanning the spectral range from 415 to 1593 nm, with 11 transmission bands. Numerical simulation suggests that, in the case of single-mode propagation of pulses with such energy in the fibre, the supercontinuum may span 14 transmission bands and have a spectral width above three octaves, with a long-wavelength edge at 4200 nm.